2017
DOI: 10.1016/j.idm.2017.11.001
|View full text |Cite|
|
Sign up to set email alerts
|

Silent circulation of poliovirus in small populations

Abstract: BackgroundSmall populations that have been isolated by conflict make vaccination and surveillance difficult, threatening polio eradication. Silent circulation is caused by asymptomatic infections. It is currently not clear whether the dynamics of waning immunity also influence the risk of silent circulation in the absence of vaccination. Such circulation can, nevertheless, be present following a declaration of elimination as a result of inadequate acute flaccid paralysis surveillance (AFPS) or environmental su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(50 citation statements)
references
References 14 publications
2
45
3
Order By: Relevance
“…These models generally agree that in most realistic situations, 3 years without any detected cases implies at least 95% confidence about no circulation, although our studies show that results depend on surveillance quality, serotype, seasonality, and vaccination strategies (Kalkowska, Duintjer Tebbens, Pallansch, et al., 2015; Kalkowska et al., 2012). In contrast to the prior literature, Vallejo et al. (2017) prominently reported (in their abstract) a 22% chance of at least 3 years between successive polio cases in a population of 10,000 people despite a 100% case detection rate.…”
Section: Introductioncontrasting
confidence: 59%
See 2 more Smart Citations
“…These models generally agree that in most realistic situations, 3 years without any detected cases implies at least 95% confidence about no circulation, although our studies show that results depend on surveillance quality, serotype, seasonality, and vaccination strategies (Kalkowska, Duintjer Tebbens, Pallansch, et al., 2015; Kalkowska et al., 2012). In contrast to the prior literature, Vallejo et al. (2017) prominently reported (in their abstract) a 22% chance of at least 3 years between successive polio cases in a population of 10,000 people despite a 100% case detection rate.…”
Section: Introductioncontrasting
confidence: 59%
“…Motivated by the re-emergence in Borno, a recent study used a stochastic model to examine whether simple, small, hypothetical populations not reached at all by vaccination can perpetuate WPV transmission while experiencing very long intervals between polio cases (Vallejo, Keesling, Koopman, & Singer, 2017). The potential for silent circulation influences the confidence about the interruption of poliovirus transmission as a function of time after the last detected poliovirus, which informs the decision to certify wild poliovirus eradication in a country, region, and globally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although overcrowding associated with urban growth, as well as ensuing sanitation issues, has been determined conducive to polio virus transmission, polio cases have been found both in urban and rural settings (Chaturvedi et al, ; Maru, Getahun, & Hoshna, ). Contemporary epidemiological studies have shown that small populations have the potential to sustain prolonged silent circulation (i.e., asymptomatic spread of polio), with an upper bound of 15 years between two successive paralytic cases (Vallejo, Keesling, Koopman, & Singer, ). On the other hand, computer modelling suggests that isolated subpopulations of less than 4,000 cannot sustain endogenous transmission of wild polio virus for more than 5 years (Duintjer Tebbens, Kalkowska, & Thompson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently annual cases of AFP is greater than 50,000 then what is the meaning of Polio free country? 4 In India, Uttar Pradesh and other states, disease and poverty are the main hurdle in polio vaccination than political, religious, culture. 5 As per report of Times of India, minimum three polio vaccines batches which contain 1.5 lakh vials reported contaminated with polio virus type 2. WHO and the Ministry of Health started surveillance, especially in Uttar Pradesh, Telangana and Maharashtra where cases of contaminated vaccines reported at large level.…”
mentioning
confidence: 99%